When hydrogen bond tailors molecular packing in non-anisometric molecules. The case study of N-alkyl 1, 3-diphenyl-4, 5-dihydro-1H-pyrazole-5-carboximidamides. Issue 3 (19th February 2021) - Kotian, Sumana Y.; D, Shridevi; Ningaiah, Srikantamurthy; Merlo, Aloir A.; Vieira, André A.; Bechtold, Ivan H.; Rai, K. M. Lokanatha
ABSTRACT: In this paper, we report the synthesis of novel liquid crystals (LCs) based on 5-membered pyrazoline heterocycle. The synthesis of pyrazoline derivative was carried out by [3 + 2] 1, 3-dipolar cycloaddition reaction of benzaldehyde phenyl hydrazone (1 ) with acrylonitrile, mediated by chloramine-T as the oxidising agent, followed by addition of hydroxylamine hydrochloride, and subsequently alkylated with various alkyl chains to afforded the title compounds. The LCs properties were investigated using differential scanning calorimetry and polarising optical microscopy. For title compounds with longer alkyl chains, monotropic columnar hexagonal mesophase was characterised by XRD analysis. The mesophase-formation was driven by intermolecular hydrogen bonds despite their non-discoid molecular structure. GRAPHICAL ABSTRACT: uf0001